Meningkatkan Motivasi Dan Prestasi Belajar Akuntansi Melalui Model Discovery Learning Pada Siswa Kelas XI AK. 1 SMK St. Willibrodus Betun Tahun Pelajaran 2022/ 2023 - Gertrudis Basilisa Bere (Universitas Palangka Raya, 2023)
SMK St. Willibrodus Betun is actively pursuing various educational projects in the field of teacher accreditation. Due to a lack of creativity and innovation in teaching strategies, students are less motivated to learn. The aim of this research is to facilitate academic progress among Grade 11 students at a faster pace. The above objectives will be achieved through the use of the Learning Discovery Model which is available for students of class XI AK.1 for the 2022-2023 academic year at SMK St. Willibrodus Betun. The purpose of this study was to determine the effect of the Discovery Learning model on student learning outcomes and skills. This study used a sample of 22 students of class XI Ak. 1. The results showed that the average score of students who were classified as